Efficient electrolyzed water catalyst with nickel-based chalcogenide heterostructure and application of efficient electrolyzed water catalyst

By using a catalyst with a nickel-based chalcogen heterostructure during the electrolytic seawater hydrogen production process, the problem of changes and reconstruction of the cathode catalyst structure is solved, efficient and stable hydrogen generation is achieved, and cost demand is reduced.

CN119615246APending Publication Date: 2025-03-14WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411703902.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

During the process of electrolyzing seawater hydrogen production, the cathode catalyst is prone to structural changes and reconstruction, resulting in catalyst damage and performance degradation. The prior art relies on precious metal Pt-based materials, which is expensive.

Method used

Using a high-efficiency electrolytic catalyst with a nickel-based chalcogen heterostructure, Ni(OH)2 nanosheets were grown on carbon cloth by hydrothermal method, and annealed with sulfur powder or selenium powder to form nanosheets with Turing structure or hollow structures, enhancing the stability and activity of the catalyst.

Benefits of technology

It realizes efficient hydrogen production in seawater electrolyzed under alkaline conditions, maintains high activity and stability for a long time, reduces the use of precious metal catalysts, and has a simple process to expand production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615246A_ABST
    Figure CN119615246A_ABST
Patent Text Reader

Abstract

According to the efficient electrolytic water catalyst with the nickel-based chalcogenide heterostructure and the application, ammonium fluoride, urea and nickel salt in different mass ratios are subjected to hydrothermal treatment, a nickel hydroxide material with a hexagonal nanosheet structure is grown on carbon cloth, the contact area with sulfur powder or selenium powder in the annealing process can be increased, and the catalytic activity of the catalyst is improved; therefore, the complete morphology is maintained after annealing. The prepared efficient seawater electrolysis oxygen evolution catalyst has the following advantages: (1) due to the uneven morphology, the catalytic activity area is increased, and hydrogen can escape from the surface; (2) the electronic structure of the nickel-based catalyst interface can be accurately regulated and controlled to improve the catalytic activity, so that the seawater electrolysis catalyst with high activity, high selectivity and lasting stability is obtained; and (3) the method is simple and easy to obtain, simple and convenient to prepare and operate, high in controllability and universal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water electrolysis hydrogen production catalysts, and in particular to a nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst and application thereof. Background Art

[0002] Hydrogen production from fossil fuels is the mainstream hydrogen production method in China, accounting for 78% of the total hydrogen production capacity. In the context of energy transformation and low-carbon development, the high carbon emissions and environmental pollution of traditional gray hydrogen production methods are prominent. Green hydrogen, produced by electrolyzing water with renewable energy, has almost no greenhouse gas emissions and is the key to achieving carbon neutrality and large-scale application of clean energy. The technology of hydrogen production by electrolysis of seawater stands out with its abundant marine resources and intermittent energy such as wind, solar and tidal energy available near the sea, which has promoted the development of green hydrogen.

[0003] In the process of seawater electrolysis, there are two main obstacles: (1) the chlorine evolution reaction (CER) competing with the oxygen evolution reaction (OER) at the anode; and (2) the formation of insoluble precipitates such as Mg(OH)2 and Ca(OH)2 on the electrode surface when the hydrogen evolution reaction (HER) occurs at the cathode. People have always paid attention to how to improve the anode OER selectivity to avoid CER, and have designed many materials that significantly improve the OER catalytic efficiency, such as NiFe / NiSx / Ni, NiMoN@NiFeN / NF, MnMoW-oxide and NiCo-UMOFNs. However, in the application of seawater electrolysis, the first choice for the cathode is still the precious metal Pt-based material. Although platinum group metals show excellent catalytic activity in hydrogen production by seawater electrolysis, their rarity and high price limit their popularity in industrial-scale applications. In view of this, researchers have begun to turn to finding more economical and affordable alternatives. In recent years, chalcogenides, phosphides, nitrides and carbides based on transition metals (such as iron, cobalt, nickel, etc.) that are abundant on Earth have attracted attention due to their potential as HER electrocatalysts. Studies have shown that these transition metal-based catalysts exhibit catalytic efficiency comparable to that of platinum group metals in the process of hydrogen production by electrolysis of seawater.

[0004] Nickel-based chalcogenides have attracted attention in the field of electrocatalysis because their crystal defects and surface active sites are conducive to regulating hydrogen adsorption energy and enhancing interfacial charge transfer. It has been confirmed that in the OER environment, the heterojunction formed by nickel-based chalcogenides will undergo structural or compositional changes, or form new phases. On the other hand, there are not many studies on the structural and compositional changes of catalysts during the HER process, and it is generally believed that the catalysts remain stable. However, existing studies have shown that nickel-sulfur catalysts also undergo phase changes and reconstruction during the HER process. Therefore, developing strategies to limit catalyst reconstruction and phase changes during the HER process is of great significance for reducing catalyst damage and improving the performance of seawater electrolysis for hydrogen production. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a nickel-based sulfide heterostructured high-efficiency water electrolysis catalyst and its application.

[0006] The technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst, and the preparation method thereof comprises the following steps:

[0007] S1: The carbon cloth is placed in a mixed solution containing urea, ammonium fluoride and nickel salt, and a hydrothermal reaction is performed to form Ni(OH)2 smooth nanosheets grown on the carbon cloth, which are denoted as Ni(OH)2@CC.

[0008] S2: The Ni(OH)2@CC obtained in step S1 is washed and dried, and then annealed with sulfur powder to form nanosheets with a Turing structure or a hollow structure, which is recorded as Turing NiS2-NiS@CC or NiS2@CC.

[0009] When the ratio of the mixed solution to the sulfur powder is 1 mL:(2-8) mg, a Turing structure nanosheet is obtained; when the ratio of the mixed solution to the sulfur powder is 1 mL:(8-40) mg, a hollow structure nanosheet is obtained.

[0010] Preferably, in step S1, the molar ratio of urea, ammonium fluoride and nickel salt is (8-33):(5-21):3.

[0011] Preferably, in step S1, the temperature of the hydrothermal reaction is 110° C.-140° C., and the time is 6-12 h.

[0012] Preferably, in step S1, the nickel salt is selected from at least one of nickel nitrate hexahydrate, nickel acetate tetrahydrate, nickel chloride tetrahydrate, and nickel sulfate heptahydrate.

[0013] Preferably, in step S2, the annealing condition is annealing at 300-500° C. in an argon atmosphere for 1-3 hours.

[0014] Preferably, the ratio of the mixed solution to sulfur powder is 1 mL: (2-40) mg.

[0015] Preferably, the method further comprises step S3: subjecting the NiS2@CC prepared in step S2 to an annealing reaction with selenium powder to obtain porous coral-like nanosheets, which are denoted as NiSe2-NiS@CC.

[0016] Preferably, in step S3, the annealing condition is annealing at 300-500° C. in an argon atmosphere for 1-3 hours.

[0017] Preferably, the ratio of the mixed solution, sulfur powder and selenium powder is 1 mL: (8-40) mg: (2-16) mg.

[0018] The second aspect of the present invention is to provide a highly efficient water electrolysis catalyst of the nickel-based sulfide heterostructure as described above for use in the electrolysis of seawater under alkaline conditions.

[0019] The beneficial effects of the present invention are as follows:

[0020] 1. The present invention uses a hydrothermal method to grow nickel hydroxide material on carbon cloth using ammonium fluoride, urea and nickel salt in different mass ratios. The nickel hydroxide presents a uniformly distributed hexagonal nanosheet structure with a side length of 4-5 microns, which can increase the contact area with sulfur powder or selenium powder during annealing, thereby maintaining a complete morphology after annealing. The carbon cloth provides a three-dimensional structure, which is conducive to increasing the conductivity of the material, and the hydrothermal method is convenient for controlling the morphology of the material. The present invention has a simple preparation process, is easy to operate, has a high oxygen production efficiency, and can be used for large-scale production.

[0021] 2. The Turing NiS2-NiS@CC prepared in one embodiment of the present invention has a special Turing structural morphology. The uneven morphology increases the contact area with the electrolyte during electrolysis and is also beneficial to the escape of bubbles when hydrogen is generated, which also means that Turing NiS2-NiS@CC has better catalytic activity. When Turing NiS2-NiS@CC undergoes a phase transition during the HER process of electrolysis of seawater, dynamic stripe creeping will occur, which can inhibit reconstruction and alkali metal hydroxide precipitation nucleation on the surface, so that the catalyst maintains high activity and stability for a long time.

[0022] 3. The NiSe2-NiS@CC prepared in one embodiment of the present invention has a porous coral morphology, and its abundant void gaps increase the contact area with the electrolyte during the electrolysis process, which also means that NiSe2-NiS@CC has better catalytic activity; in the process of HER electrolysis of seawater, the hydrogen evolution efficiency and stability of NiSe2-NiS@CC are greatly improved compared with single-phase NiS@CC, because the selenium atoms in the heterojunction can anchor the sulfur atoms to avoid their precipitation and oxidation during the electrolysis process, and the sulfur atoms as an active phase promote the catalytic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0024] Figure 1Scanning electron microscope images of Ni(OH)2@CC(a) and Turing NiS2-NiS@CC(b) in Example 1;

[0025] Figure 2 XRD patterns of Turing NiS2-NiS@CC, NiS2@CC and NiS@CC in Example 1, Example 2 and Comparative Example 1;

[0026] Figure 3 The Raman spectra of Turing NiS2-NiS@CC, NiS2@CC and NiS@CC in Example 1, Example 2 and Comparative Example 1;

[0027] Figure 4 Ni 2p fine XPS spectrum of Turing NiS2-NiS@CC in Example 1;

[0028] Figure 5 HER performance comparison diagram (LSV curve) of Turing NiS2-NiS@CC, NiS2@CC and NiS@CC in simulated seawater (1M KOH+1M NaCl) in Example 1, Example 2 and Comparative Example 1;

[0029] Figure 6 HER stability diagram (it curve) of Turing NiS2-NiS@CC in real seawater and simulated seawater (1M KOH+1M NaCl) in Example 1;

[0030] Figure 7 XRD patterns of NiSe2-NiS@CC, NiSe2@CC and NiS@CC in Example 3, Comparative Example 2 and Comparative Example 3;

[0031] Figure 8 The scanning electron microscope images of NiS2@CC (a) and NiSe2-NiS@CC (b) in Example 2 and Example 3;

[0032] Fig. 9 The scanning electron microscope images of NiSe2-NiS@CC before and after the reaction in Example 3;

[0033] Fig.10 HER performance comparison diagram (LSV curve) of NiSe2-NiS@CC, NiSe2@CC, and NiS@CC in simulated seawater (1M KOH+1M NaCl) in Example 3, Comparative Example 2, and Comparative Example 3;

[0034] Fig.11 This is the HER stability diagram (iT curve) of NiSe2-NiS@CC in real seawater in Example 3. DETAILED DESCRIPTION

[0035] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0036] Example 1

[0037] A piece of carbon cloth (CC) was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form Ni(OH)2 smooth nanosheets grown on CC, recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. After the obtained product was dried at 60 ° C for 1 hour, it was annealed in an argon atmosphere at 450 ° C in a tube furnace for 1 hour and reacted with 50 mg of sulfur powder to form a nanostructure with a special Turing structure, recorded as Turing NiS2-NiS@CC.

[0038] Example 2

[0039] A piece of CC was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form a smooth Ni(OH)2 nanosheet grown on CC, which was recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. After the obtained product was dried at 60 ° C for 1 hour, it was annealed in an argon atmosphere in a 450 ° C tube furnace for 1 hour. According to the amount of sulfur powder used, 80 mg, a porous nanosheet structure was formed, which was recorded as NiS2@CC. The NiS2@CC in this example is used as a comparison sample of Turing NiS2-NiS@CC.

[0040] Example 3

[0041] A piece of CC was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form a smooth Ni(OH)2 nanosheet grown on CC, which was recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. After the obtained product was dried at 60 ° C for 1 hour, it was annealed in an argon atmosphere in a 450 ° C tube furnace for 1 hour. According to the amount of sulfur powder used, 250 mg, a porous nanosheet structure was formed, which was recorded as NiS2@CC. NiS2@CC was further annealed in an argon atmosphere in a 450 ° C tube furnace for 1 hour and reacted with 120 mg of selenium powder to obtain a porous coral-like nanostructure, which was recorded as NiSe2-NiS@CC.

[0042] Comparative Example 1

[0043] A piece of CC was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form a smooth Ni(OH)2 nanosheet grown on CC, which was recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. After the obtained product was dried at 60 ° C for 1 hour, it was annealed in an argon atmosphere at 450 ° C in a tube furnace for 1 hour and reacted with 50 mg of sulfur powder to form a nanostructure with a special Turing structure, which was recorded as Turing NiS2-NiS@CC. Turing NiS2-NiS@CC was annealed in an argon atmosphere at 450 ° C in a tube furnace for 1 hour (without sulfur powder) to obtain NiS@CC.

[0044] Comparative Example 2

[0045] A piece of CC was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form Ni(OH)2 smooth nanosheets grown on CC, recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. The obtained product was dried at 60 ° C for 1 hour, annealed in an argon atmosphere at 450 ° C in a tube furnace for 1 hour, and reacted with 120 mg of selenium powder to obtain NiSe2@CC.

[0046] Comparative Example 3

[0047] A piece of CC was placed in a mixed solution of 25 mL of urea, ammonium fluoride and nickel nitrate, and transferred to a 50 mL stainless steel autoclave. The polytetrafluoroethylene-lined autoclave was kept at 120 ° C for 6 hours to form a smooth Ni(OH)2 nanosheet grown on CC, which was recorded as Ni(OH)2@CC; after hydrothermal treatment, the obtained sample was repeatedly rinsed with deionized water and ethanol alternately. After the obtained product was dried at 60 ° C for 1 hour, it was annealed in an argon atmosphere in a 450 ° C tube furnace for 1 hour. According to the amount of sulfur powder used, 250 mg, a porous nanosheet structure was formed, which was recorded as NiS2@CC. NiS2@CC was further annealed in an argon atmosphere in a 450 ° C tube furnace for 1 hour to obtain NiS@CC.

[0048] Figure 1The scanning electron microscope images of Ni(OH)2@CC (left) and Turing NiS2-NiS@CC (right) in Example 1. The smooth nanosheet structure of Ni(OH)2@CC was successfully transformed into Turing NiS2-NiS@CC with Turing structure after annealing and sulfurization, indicating that Turing NiS2-NiS@CC was successfully synthesized.

[0049] Figure 2 The XRD patterns of Turing NiS2-NiS@CC, NiS2@CC and NiS@CC in Example 1, Example 2 and Comparative Example 1. The Turing NiS2-NiS@CC heterojunction maintains a relatively stable crystal structure of NiS2 and NiS phases during its formation.

[0050] Figure 3 The Raman spectra of Turing NiS2-NiS@CC, NiS2@CC and NiS@CC in Example 1, Example 2 and Comparative Example 1 are shown. Compared with NiS2@CC and NiS@CC, the characteristic peaks of Turing NiS2-NiS@CC have obvious shifts and deformations. This indicates that there is a strong electronic interaction between NiS2@CC and NiS@CC.

[0051] Figure 4 Ni 2p fine XPS spectrum of Turing NiS2-NiS@CC in Example 1. Compared with NiS2@CC and NiS@CC, Turing NiS2-NiS@CC has metallic Ni (Ni 0 ) characteristic peaks. This indicates that NiS2-NiS@CC is an excellent metal conductor. 0 It can effectively capture electrons and provide a pathway for electron transfer, thus acting as an active center in the electrocatalytic process.

[0052] Figure 5 The HER performance comparison diagram (LSV curve) of Turing NiS2-NiS@CC and its comparison sample in simulated seawater (1M KOH+1M NaCl) in Example 1, Example 2 and Comparative Example 1. The performance of Turing NiS2-NiS@CC is much better than that of NiS2@CC and NiS@CC, indicating that Turing NiS2-NiS@CC can be used in electrolysis of seawater.

[0053] Figure 6This is the HER stability diagram (iT curve) of Turing NiS2-NiS@CC in real seawater and simulated seawater (1M KOH+1M NaCl) in Example 1. Turing NiS2-NiS@CC can remain stable for a long time at different current densities in seawater, indicating that Turing NiS2-NiS@CC can be used in the electrolysis of seawater.

[0054] Figure 7 XRD spectra of NiSe2-NiS@CC, NiSe2@CC and NiS@CC in Example 3, Comparative Example 2 and Comparative Example 3. NiSe2-NiS@CC contains characteristic peaks of NiSe2 and NiS, indicating the successful preparation of the heterojunction.

[0055] Figure 8 The scanning electron microscope images of NiS2@CC (left) and NiSe2-NiS@CC (right) in Examples 2 and 3. Compared with NiS2@CC, NiSe2-NiS@CC has more pores, indicating that the addition of selenium changes the morphology of the catalyst. More pores means a larger contact area with the electrolyte, and the catalytic efficiency is improved.

[0056] Fig. 9 The scanning electron microscope images of NiSe2-NiS@CC before and after the reaction in Example 3. There is no difference in the morphology of NiSe2-NiS@CC before and after the reaction, indicating that the selenium atoms in the catalyst can anchor the sulfur atoms to prevent their precipitation and oxidation during the electrolysis process, thereby maintaining the catalytic performance of the catalyst.

[0057] Fig.10 The HER performance comparison diagram (LSV curve) of NiSe2-NiS@CC, NiSe2@CC and NiS@CC in simulated seawater (1M KOH+1M NaCl) in Example 3, Comparative Example 2 and Comparative Example 3. The performance of NiSe2-NiS@CC is much better than that of NiSe2@CC and NiS@CC, indicating that NiSe2-NiS@CC can be used in the electrolysis of seawater.

[0058] Fig.11 This is the HER stability diagram (iT curve) of NiSe2-NiS@CC in real seawater in Example 3. NiSe2-NiS@CC can remain stable for a long time at high current density in seawater, indicating that NiSe2-NiS@CC can be used in the electrolysis of seawater.

[0059] Electrocatalytic Applications

[0060] The nanomaterials prepared in Examples 1-3 were used as working electrodes, and the linear sweep voltammetric curves of the catalysts were measured in a three-electrode system (a platinum wire electrode was used as the working electrode, and a saturated Ag / AgCl electrode was used as the reference electrode) in simulated seawater containing 1M KOH+1M NaCl. When producing hydrogen, the current density of the sample in Example 1 was 10 mA cm -2 When the overpotential is 47 mV, the current density of the sample in Example 2 is 10 mA cm -2 When the overpotential is 67 mV, the current density of the sample in Example 3 is 10 mA cm -2 When , the overpotential is 26mV.

[0061] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A nickel-based sulfide heterostructured high-efficiency water electrolysis catalyst, characterized in that: The preparation method thereof comprises the following steps: S1: The carbon cloth is placed in a mixed solution containing urea, ammonium fluoride and nickel salt, and a hydrothermal reaction is performed to form Ni(OH)2 smooth nanosheets grown on the carbon cloth, which are denoted as Ni(OH)2@CC. S2: The Ni(OH)2@CC obtained in step S1 is washed and dried, and then annealed with sulfur powder to form nanosheets with a Turing structure or a hollow structure, which is recorded as Turing NiS2-NiS@CC or NiS2@CC.

2. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: In step S1, the molar ratio of urea, ammonium fluoride and nickel salt is (8-33):(5-21):

3.

3. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: In step S1, the temperature of the hydrothermal reaction is 110°C-140°C, and the time is 6-12 hours.

4. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: In step S1, the nickel salt is selected from at least one of nickel nitrate hexahydrate, nickel acetate tetrahydrate, nickel chloride tetrahydrate, and nickel sulfate heptahydrate.

5. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: In step S2, the annealing condition is annealing at 300-500° C. in an argon atmosphere for 1-3 hours.

6. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: The ratio of mixed solution to sulfur powder is 1mL:(2-40)mg.

7. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 1, characterized in that: The method further comprises step S3: annealing the NiS2@CC prepared in step S2 with selenium powder to obtain porous coral-like nanosheets, which are denoted as NiSe2-NiS@CC.

8. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 7, characterized in that: In step S3, the annealing condition is annealing at 300-500° C. in an argon atmosphere for 1-3 hours.

9. The nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst according to claim 7, characterized in that: The ratio of mixed solution, sulfur powder and selenium powder is 1mL:(8-40)mg:(2-16)mg.

10. Use of the nickel-based sulfide heterostructure high-efficiency water electrolysis catalyst as described in any one of claims 1 to 9 in the electrolysis of seawater under alkaline conditions.